World Intellectual Property Report 2024 : Making Innovation Work for Development. (World Intellectual Property Organization, 2024)
"Combining economic analysis with in-depth industry studies, the 2024 edition of the World Intellectual Property Report introduces a new data-driven methodology designed to help policymakers make informed decisions by leveraging existing local innovation capabilities and strengthen their national innovation ecosystems. Complementing this framework are three case studies across the agriculture technology, motorcycle and video game industries, spanning eight different countries. These studies demonstrate how countries have successfully carved out specialized trajectories within innovative and complex industries."-- Provided by publisher
Keywords: Intellectual property -- Economic aspects.; Technological innovations -- Government policy.; Technological innovations -- Economic aspects.